Polygamy in Islam: Its Relevance to the Social Development of Sulu - Murphy, Pemor (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study looks into how polygamy plays a role in the social growth of the Tausug community in Sulu, Philippines, focusing on its religious approval under Shari’ah law. Based on Islamic teachings, polygyamy isn't just a cultural tradition or personal choice—it's seen as a social institution that helps tackle issues like widowhood, gender imbalance, and creating resilient family units that can handle economic challenges. To acquire these, we employed methods like focus group discussions and interviews with religious scholars (Ulama), community leaders, and polygamous married couples. We monitored their attitudes and actions toward polygamy in different areas of Sulu. What we discovered is that most ulama are firm supporters of polygamy, that as long as it is practiced according to the Islamic teachings—being fair, equal, and economically capable—it can solidify the family and alleviate poverty and sinful acts. Hurdles to this, however, are a lack of general information on Islamic laws of marriage, premarital education is not practiced, and emotional or financial unreadiness. These issues sometimes lead to conflict and negative attitudes towards polygamy. The study is based on two basic theories: structural functionalism, which considers polygamy as fulfilling society's needs, and symbolic interactionism, which studies how cultural and religious interactions shape the perception of marriage. Limitations include a small sample size and some potential bias since the researcher’s own cultural background and interpretations might influence the findings. We also referenced the Qur'an (Surah An-Nisa 4:3) and authentic Hadiths to emphasize the spiritual roots of polygamy, and we’ve taken care to cite these more thoroughly. The study recommends that each couple be provided with access to Islamic family law training, Shari'ah courts, religious functionaries, and the local government. The study also recommends economic support schemes and public information campaigns to offset myths and encourage responsible practice of polygamy as a healthy community development force for the Tausug.